Enhancing Hydrophilicity of Thick Electrodes for High Energy Density Aqueous Batteries - Lee, Jungeun; Lee, Hyeonsoo; Bak, Cheol; Hong, Youngsun; Joung, Daeha; Ko, Jeong Beom; Lee, Yong Min; Kim, Chanhoon (Nano-Micro Letters, 2023)
Thick electrodes can substantially enhance the overall energy density of batteries. However, insufficient wettability of aqueous electrolytes toward electrodes with conventional hydrophobic binders severely limits utilization of active materials with increasing the thickness of electrodes for aqueous batteries, resulting in battery performance deterioration with a reduced capacity. Here, we demonstrate that controlling the hydrophilicity of the thicker electrodes is critical to enhancing the overall energy density of batteries. Hydrophilic binders are synthesized via a simple sulfonation process of conventional polyvinylidene fluoride binders, considering physicochemical properties such as mechanical properties and adhesion. The introduction of abundant sulfonate groups of binders (i) allows fast and sufficient electrolyte wetting, and (ii) improves ionic conduction in thick electrodes, enabling a significant increase in reversible capacities under various current densities. Further, the sulfonated binder effectively inhibits the dissolution of cathode materials in reactive aqueous electrolytes. Overall, our findings significantly enhance the energy density and contribute to the development of practical zinc-ion batteries. Highlights: 1 Sulfonated polyvinylidene fluoride (S-PVdF) binders with improved hydrophilicity were synthesized via a simple sulfonation process of conventional hydrophobic PVdF binders. 2 The abundant sulfonate groups of S-PVdF binders significantly improved ionic conduction in thick electrodes ( 6 mg cm−2), enabling improved reversible capacities under various current densities. 3 The S-PVdF binders effectively suppressed cathode dissolution, resulting in enhanced capacity retention at higher temperature operations (45 °C).